1987
DOI: 10.1002/j.1460-2075.1987.tb02390.x
|View full text |Cite
|
Sign up to set email alerts
|

lac repressor forms loops with linear DNA carrying two suitably spaced lac operators.

Abstract: Tetrameric lac repressor may bind to two lac operators on one DNA fragment and induce the intervening DNA to form a loop. Electron microscopy, non-denaturing polyacrylamide gel electrophoresis, and DNase I protection experiments were used to demonstrate such DNA loops, where the distance between the centres of symmetry of the two lac operators varies between 63 and 535 bp. Formation of a DNA loop is favoured by correct phasing of the two lac operators and a low concentration of both components of the reaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
259
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 352 publications
(286 citation statements)
references
References 50 publications
22
259
1
Order By: Relevance
“…132 This result agrees with the observations by Hsieh et al using the filter binding assay, whose quantitative results are shown in Figure 8. 133 This disagreement in the behavior of the looping free energy as the distance between operators decreases between the in vivo and in vitro experiments is a stark reminder of the challenge of reconciling the in vitro and in vivo pictures of DNA mechanics in general, and proteinmediated looping in specifically.…”
supporting
confidence: 92%
“…132 This result agrees with the observations by Hsieh et al using the filter binding assay, whose quantitative results are shown in Figure 8. 133 This disagreement in the behavior of the looping free energy as the distance between operators decreases between the in vivo and in vitro experiments is a stark reminder of the challenge of reconciling the in vitro and in vivo pictures of DNA mechanics in general, and proteinmediated looping in specifically.…”
supporting
confidence: 92%
“…As we explain below, knowledge of the location of cleavage enhancement or suppression sites can be used to obtain information about the structure of looped DNA in solution. Our analysis of the DNase I footprinting profiles of short, LacRmediated loops (20) indicates that, under the conditions of these experiments, the tetramer adopts the E state.…”
mentioning
confidence: 73%
“…Thus, the cutting activity of DNase I should not be affected by loop formation, and, indeed, no enhancement of DNase I cutting is observed for the wild-type O1-O3 loop (29) and the pHK59 loop (20).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations